Income inequality in Germany stagnating over the long term, but decreasing slightly during the coronavirus pandemic - Markus M. Grabka (DIW Weekly Report, 2021)
Both wages and needs-adjusted household income increased by ten percent between 2013 and 2018, benefiting all income groups. Wage inequality has been declining for many years and has now again reached the level of the early 2000s. At the same time, the low-wage sector shrank by two percentage points. Household income inequality, in contrast, has hardly changed for many years and the low-income rate is stagnating. However, the share of people in Germany who are affected by severe material deprivation sank to a low level in a European comparison. Income inequality in Germany has declined slightly since the beginning of the coronavirus pandemic, but this is likely primarily due to incomes decreasing among the self-employed. However, the pandemic poses the risk that an increasing number of insolvencies and unemployed people will cause incomes to fall again across the board. Financial assistance for the self-employed and business owners should not be ended too early and its targeting should be readjusted.
Keywords: D31; I31; I32; 330; Income inequality; poverty; SOEP